Preface to the symposium 40 years from Alma-Ata. Primary Health Care - Pacheco Romero, José (2018)
Four decades have passed since the World Health Organization (WHO) carried out the most important health meeting with the nations of the world, the Primary Health Care, with the purpose of changing the paradigm in health care . Already during the twenty-eighth WHO Assembly in 1975, the urgent need for new approaches to health care for all and for all, from an individualized and medicalized approach to a social approach, with profound respect for human rights, was identified. . The phrase 'Health for All in the Year 2000' was coined.